Population-based stroke risk profile from a West-African community - Ifeoma Uchenna Onwuakagba; Emmanuel Chiebuka Okoye; Favour Chidera Kanu; Chukwuemeka Michael Kalu; Daniel Chidubem Akaeme; Ogochukwu Charity Obaji; Christopher Olusanjo Akosile (eNeurologicalSci, 2023)
Objectives: To determine the stroke risk profile of dwellers of Nnewi community in Nigeria. Methods: This was a cross-sectional survey involving consecutively recruited community-dwelling adults without a previous history of stroke. The Modified Framingham Stroke Risk Score (MFSRS) was used to evaluate the stroke risk profile of the participants. Data was analysed using descriptive and inferential statistics at an alpha level of 0.05. Result: 310 individuals (mean age = 37.21 ± 15.84 years; 68.7% females) participated in this study. The mean MFSRS (6.79 ± 5.21) of the participants was minimal with 16% having a moderate-to-high risk. Dyslipidaemia (100.0%), meat (88.1%) and sugar (70.6%) consumption, hypertension (37.7%), physical inactivity (43.2%), and psychological stress (41.3%) were the most prevalent risk factors in the population. Participants' MFSRS significantly and positively correlated with their body mass index (BMI), waist circumference (WC), and waist-hip ratio (WHR) and significantly differed across their gender, educational, and occupational categories (p < 0.05). Conclusion: According to MFSRS, the risk of stroke among the sampled community was minimal and was significantly influenced by their BMI, WC, WHR, gender, education, and occupation. However, results revealed that stroke risk might be higher in the population than was depicted by the MFSRS. Enlightenment on the risk of stroke is needed in the community.